Hacienda catedralicia y promoción artística en la Catedral de Mallorca (1573-1604) - Martinez Oliver, Bartolome (Cauriensia, 2023)
The direct relation between the finances, the economy, and the cathedral treasury with the artistic promotion of the Cathedral of Palma, in times of the Valencian bishop Juan Vic y Manrique de Lara (1573-1604), is reflected in diverse documentary sources conserved in the Chapter Archive of Mallorca (ACM). Mensa capitular, books of sacristy to exhume new news related to the decency and decorum in the temple, especially, painters, silversmiths, sculptors and master builders, these last ones directed by the canon worker or major worker. We begin our journey through the written testimony of the doctor in the service of the bishop, Juan Binimelis in the work Historia General del Reino de Mallorca (1593-1595), which will serve as a starting point to verify the synergies of the diocesan and cathedral management teams at the service of art.